Natural capital for nature’s contributions to people: the case of Japan - Junya Kumagai; Mihoko Wakamatsu; Shizuka Hashimoto; Osamu Saito; Takehito Yoshida; Takehisa Yamakita; Keiko Hori; Takanori Matsui; Michio Oguro; Masahiro Aiba; Rei Shibata; Tohru Nakashizuka; et al. (Sustainability Science, 2022)
Recently, natural capital has gained the attention of researchers and policymakers to promote sustainability. Previous studies have investigated the value of ecosystem services with respect to specific areas or species. Other studies have investigated the value of various types of ecosystem services and natural capital by integrating a number of findings using meta-analyses at the global level. Although these studies have provided information on either the global value of natural capital or the local value of specific subjects, there is little evidence on the country-specific values of natural capital in Japan, which will provide useful information for national environmental policies. We investigated the perceived values of terrestrial and marine natural capital in Japan using internet surveys and payment card methods. Data on various natural forms of capital were collected in a unified format and comparable manner. We found that some explanatory variables, such as perceived importance and visit frequency, as well as sociodemographic characteristics, are significant drivers of the willingness to pay (WTP), which maintains each aspect of natural capital. In addition, we conducted future predictions of terrestrial and marine natural capital using a scenario developed in a previous study. Our results indicate that Japan should follow a population-dispersed scenario for the sustainable management of natural capital up to 2050.

The journey from white rice to ultra-high hydrostatic pressurized brown rice: an excellent endeavor for ideal nutrition from staple food - Michio Hashimoto; Shahdat Hossain; Kentaro Matsuzaki; Osamu Shido; Katsumi Yoshino (Critical Reviews in Food Science and Nutrition, 2022)

Correction to: Natural capitals for nature’s contributions to people: the case of Japan - Junya Kumagai; Mihoko Wakamatsu; Shizuka Hashimoto; Osamu Saito; Takehito Yoshida; Takehisa Yamakita; Keiko Hori; Takanori Matsui; Michio Oguro; Masahiro Aiba; Rei Shibata; Tohru Nakashizuka; et al. (Sustainability Science, 2022)
A correction to this paper has been published: https://doi.org/10.1007/s11625-021-00939-6

Docosahexaenoic Acid (DHA, C22:6, ω-3) Composition of Milk and Mammary Gland Tissues of Lactating Mother Rats Is Severely Affected by Lead (Pb) Exposure - Shahdat Hossain; Jakir Hussain; Sujan Bhowmick; Marzan Sarkar; Mafroz Basunia; Abdullah Al Mamun; Yoko Tanabe; Kentaro Matsuzaki; Michio Hashimoto; Osamu Shido (Biological Trace Element Research, 2020)

Differential effects of docoosahexaenoic and arachidonic acid on fatty acid composition and myosin heavy chain-related genes of slow- and fast-twitch skeletal muscle tissues - Michio Hashimoto; Takayuki Inoue; Masanori Katakura; Shahdat Hossain; Abdullah Al Mamun; Kentaro Matsuzaki; Hiroyuki Arai; Osamu Shido (Molecular and Cellular Biochemistry, 2016)

Proliferation of neuronal progenitor cells and neuronal differentiation in the hypothalamus are enhanced in heat-acclimated rats - Kentaro Matsuzaki; Masanori Katakura; Toshiko Hara; Guanghua Li; Michio Hashimoto; Osamu Shido (Pflügers Archiv - European Journal of Physiology, 2009)

Changes of noradrenaline-induced contractility and gene expression in aorta of rats acclimated to heat in two different modes - Guang Hua Li; Masanori Katakura; Megumi Maruyama; Budbazar Enhkjargal; Kentaro Matsuzaki; Michio Hashimoto; Osamu Shido (European Journal of Applied Physiology, 2008)

Effect of P2 receptor on the intracellular calcium increase by cancer cells in human umbilical vein endothelial cells - Namie Nejime; Naoko Tanaka; Ryoko Yoshihara; Satomi Kagota; Noriko Yoshikawa; Kazuki Nakamura; Masaru Kunitomo; Michio Hashimoto; Kazumasa Shinozuka (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Docosahexaenoic acid but not eicosapentaenoic acid withstands dietary cholesterol-induced decreases in platelet membrane fluidity - Michio Hashimoto; Shahdat Hossain; Osamu Shido (Molecular and Cellular Biochemistry, 2006)

Alterations of calf venous and arterial compliance following acclimation to heat administered at a fixed daily time in humans - Megumi Maruyama; Toshiko Hara; Michio Hashimoto; Miki Koga; Osamu Shido (International Journal of Biometeorology, 2006)

Protective effects of nicaraven, a new hydroxyl radical scavenger, on the endothelial dysfunction after exposure of pig coronary artery to hydroxyl radicals - Mohammed Shah Alam; Kwansong Ku; Masanobu Yamauchi; Michio Hashimoto; Seishi Nosaka; Mohammed Shadat Hossain; Sumio Masumura; Kengo Nakayama; Katsuhiro Tamura (Molecular and Cellular Biochemistry, 1998)